(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2026)
The translation of historical texts presents unique challenges, especially when conveying the cultural, historical and linguistic features of the original work. This article examines the translation methods used in the translation of Baburnama, the memoirs of Zahir-ud-Din Muhammad Babur, focusing on literal translation, dynamic equivalence and cultural substitution. By analyzing different translation strategies, the article highlights how these methods affect the accuracy, readability and cultural authenticity of historical texts. Through the case study of Baburnama, this research underscores the importance of balancing linguistic precision and accessibility to ensure the original context and essence are preserved for modern audiences.